Влияние надежности сельхозтехники на вероятность выполнения технологических процессов - Невзоров, А. В.; Ковальчук, Ю. А.; Дидур, В. В.; Дідур, В. В.; Nevzorov, Andrey; Kovalchuk, Yuri; Didur, Vladimir (КНТУ, 2015)
Разработана методика определения соответствия комплексов сельскохозяйственных машин производственной технологии. Решение принимается по результатам вычисления вероятности того, что выполнение сельскохозяйственных работ будет большим, чем минимально допустимое значение, и сравнения этой вероятности с пороговым значением. Розроблено методику визначення відповідності комплексів сільськогосподарських машин виробничій технології. Рішення приймається за результатами обчислення ймовірності того, що виконання сільськогосподарських робіт буде більшим, ніж мінімально допустиме значення, і порівняння цієї ймовірності з пороговим значенням. When performing many works downtime due to machine failure lead to irretrievable loss of the products or reduction in other benefits. For example, agricultural failures lead to lost production because the yield of crops depends on the timing of technological operations. Purpose of the article - to determine the probability of unacceptable loss of production due to machine failure in the performance of technological operations (for example, processes of crop). Since the reliability and performance of machines increases, the time between when the machine operation is often less than or comparable to the MTBF. In this case, even a single complex failures may significantly increase the duration of work and lead to an unacceptable loss of production (in this case, the production task is failed). Therefore, taking into account the recommendations [11], should also determine the probability of the job (the probability that the loss does not exceed the permissible value). On the basis of the account of influence of failures of cars on the loss of production we have developed a new method of determining the appropriate technological complexes machinery manufacturing orders. The decision is made based on the results of calculating the likelihood that output will be greater than the minimum allowable value, and comparing this with a threshold probability. The developed method can be used in crop production and other industries where machine downtime resulting in the loss of production or reduce other benefits. The results of probabilistic calculations by this method can be used to improve the systems of maintenance of machinery (in particular - during the transition to oncondition maintenance). A limitation of this method is to perform each operation only machine.
Вплив надійності сільгосптехніки на імовірність виконання технологічних процесів
Effects of reliability for the probability of agricultural machinery performance process
Keywords: сельскохозяйственная техника; технологические процессы; отказы; вероятность безотказной работы; сільськогосподарська техніка; технологічні процеси; відмови; імовірність безвідмовної роботи; farm equipment; processes; failures; the probability of failure-free operation